Rhinomanometry to Evaluate Nose Stuffiness Objectively in Patients With Rhinitis - TAHAMİLER, Rauf and IŞILDAK, Hüseyin and ÇANAKÇIOĞLU, Salih (Cerrahpaşa Medical Journal, 2014)
Nose is an entrance for Oxygen. It is too easy to realize nose stuffiness. However the point is realizing restriction of respiration due to nose stuffiness. At this point, functional nasal examinations get more crucial. For this purpose many methods were investigated such as rhinomanometry and acoustic rinometry. In the present review, we have mentioned about rhinomanometry which is a kind of method to evaluate nasal air flowing physiology and pathology. Rhinomanometry measures barometric differences between nasopharynx and external nostrils. Rhinomanometry method can be performed three different ways; active anterior RM, active posterior RM and passive anterior RM. In our study, we performed prick test to 508 patients with rhinitis. According to their Prick test result we divided them into two groups; 393 non-allergic patients, 115 allergic patients. Afterwards, we performed rhinomanometry. As a result, there was no difference between allergic rhinitis and non-allergic rhinitis groups about their rhinomanometry measures.